2014
DOI: 10.1088/2043-6262/5/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam/ γ -ray irradiation synthesis of gold nanoparticles and investigation of antioxidant activity

Abstract: Colloidal solutions of 1 mM gold nanoparticles (AuNPs) were synthesized by γ-ray Co-60 and electron beam irradiation using 1% water soluble chitosan (WSC) with different molecular weight (Mw) as stabilizer. The AuNPs size measured from TEM images was of 7.1 and 15.1 nm for electron beam and γ-ray Co-60, respectively. The AuNPs sizes of 9.8, 15.1 and 22.4 nm stabilized by different WSC Mw of 155 × 10 3 , 78 × 10 3 and 29 × 10 3 g mol −1 , respectively, were also synthesized by γ-ray Co-60 irradiation. Antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(55 reference statements)
0
11
0
2
Order By: Relevance
“…Furthermore, the size of the synthesized PtNPs (1.4-1.6 nm) was also smaller than that of the PtNPs (3.4 nm) that were synthesized by the chemical method using NaBH 4 as a reducing agent with the same initial concentration of 1 mM Pt 4+ and 1% CTS as a stabilizer [5]. Moreover, the study on the synthesis of Ag and Au nanoparticles by the gamma Co-60 ray irradiation method using CTS as a stabilizer revealed that the size of Ag and Au nanoparticles was 4.6 and 9.8 nm for 1 mM Ag + and Au 3+ ions, respectively [16,20]. us, it is obvious that the size of PtNPs synthesized by the gamma Co-60 ray irradiation method is smaller than that of Ag and Au nanoparticles at the same initial concentration of metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the size of the synthesized PtNPs (1.4-1.6 nm) was also smaller than that of the PtNPs (3.4 nm) that were synthesized by the chemical method using NaBH 4 as a reducing agent with the same initial concentration of 1 mM Pt 4+ and 1% CTS as a stabilizer [5]. Moreover, the study on the synthesis of Ag and Au nanoparticles by the gamma Co-60 ray irradiation method using CTS as a stabilizer revealed that the size of Ag and Au nanoparticles was 4.6 and 9.8 nm for 1 mM Ag + and Au 3+ ions, respectively [16,20]. us, it is obvious that the size of PtNPs synthesized by the gamma Co-60 ray irradiation method is smaller than that of Ag and Au nanoparticles at the same initial concentration of metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…As for high-energy accelerators, the energy is around 5–10 MeV with energies up to 100 kW. For instance, the expected penetration of a high energy accelerator of 10 MeV is around ~38 mm, depending on the density of the material [ 94 , 99 ]. The technology holds high throughput and offers as an advantage a recognized operational safety and power [ 94 , 99 ].…”
Section: Radiation Technologies Applied To Gold Nanoparticlesmentioning
confidence: 99%
“…Thus, high concentration of HAuCl 4 was likely to give equal possibility for all gold clusters to grow into nano-flakes and only gold nano-flakes is able to maintain its activity in PAD for carbohydrates. In our previous study, the antioxidant efficiency of gold nano-particles decreased with its size [15] as the explanation for the stability of the gold nano-flakes in PAD condition. It should be noted that the inclination of nano-flakes in Fig.…”
Section: The Concentration Of Hauclmentioning
confidence: 80%